(untitled) (Research, Society and Development, 2022)
Objective: To analyze the use of indicators in the acquisition of medicines and other health supplies and in the supply of stocks. Methods: This is a retrospective longitudinal study carried out at the Specialized Institute in Orthopedics and Traumatology located in the city of Rio de Janeiro. The data were obtained by the researchers themselves from reports available in the hospital management system and internal control spreadsheets corresponding to the period from Jan/2019 to Dec/2020. Results: There was a drop in the receipt of items between the years 2019 (241) and 2020 (156), and in the rate approved items when comparing 2020 [37.7 (sd=22.4)] and 2019 [58.2 (sd=17.9)]. The unmet demand rate was 15.4% (sd=3.2) in 2019 and 25.7% (sd=7.1) in 2020; while the average processing time of regular processes was 14.5 months (sd=1.8) in 2020 and 9.6 months (sd=2.4) in 2019. Conclusions: The implementation of the indicators enabled the verification of deficiencies in the acquisition of medicines and other supplies since the period before the pandemic, resulting in the shortage of stocks that had its peak with COVID-19.